DETERMINANT OF SOCIAL PROTEST IN SUBSIDIZED RICE PROGRAM - Mery Yanti; Yusnaini Yusnaini; Indra Tamsyah; Gunawan Lestari Elake (Jurnal Analisa Sosiologi, 2025)
Food security is one of the major themes that has received attention from the Sustainable Development Goals (SDGs). In Indonesia, one of the government's efforts to achieve food security is to release a subsidized rice program (Program Beras Miskin or Program Raskin) that began in the Monetary Crisis in 1998. Unfortunately, the implementation of this program has always triggered social protests from the beneficiaries of the program. This article aims to analyze the determinants of social protest in the context of implementing a subsidized rice program with logistic regression techniques. Based on the 5th Indonesian Family Life Survey (IFLS) data, this article found seven independent variables can estimate social protest. This model can explain social protest significantly by 0.0515 (5.15%), X2 (7) = 428.32, p <0.01. This article recommends that the government improve the quality of governance at the district/city and village level, formulate public policy that can increase the stock of social capital at the community level, and improve equal access to primary, secondary, and higher education for citizens, to minimize social protest from the citizens.